Student Gestures in Solving Mathematics Problems in Group Discussion Activities - Masniladevi Masniladevi (Jurnal Ilmiah Sekolah Dasar, 2022)
As one of the subjects in the national education curriculum, mathematics has an important role in human life. Mathematics is not only used as a reference for continuing higher education but is also used to support one's career. However, in reality, students still find it difficult to understand the material being studied, including understanding the problems in mathematics. This study aims to analyze the use of gestures in solving mathematical problems in group discussions. This research uses qualitative research and uses exploratory, descriptive research. The research subjects selected consisted of 2 students in the low group, two in the medium group, and two in the high group based on discussions with the subject teacher. The observed gesture is when students solve problems in groups. The results of data analysis show that the gestures made by students have several variations. Students in the high group performed more gestures such as pointing, writing, and representational gestures, and they understood the problem better. Representational gestures used by high-ability students can provide conceptual understanding to their groupmates, while those with moderate and low abilities in the discussion process of solving mathematical problems are still confused in representing the intent of their problem-s.